A Field Study of Job Insecurity during a Financial Crisis - Adkins, Cheryl L.; Werbel, James D.; Farh, Jiing-Lih (Group & organization management, 2001)
A major trend in the workplace is a recognition of the increasingly temporary nature of the work relationship. Even universities, which have traditionally offered long-termjob security in the form of academic tenure, are not immune from that trend. Some universities no longer offer tenure, and financial pressures sometimes threaten the job security of tenured faculty. The increased focus on the temporary nature of the work relationship may lead to a sense of job insecurity among employees. The present study examined antecedents and outcomes of job insecurity following significant budget cuts at a major university. Perceptions of receiving sufficient and accurate information from organizational sources, tenure status, and tolerance for ambiguity predicted job insecurity. Job insecurity, in turn, predicted job satisfaction, organizational commitment, and withdrawal behaviors. Turnover for a 2-year period following the budget cuts was predicted by survey variables.